Analysis of functionally graded plates by a simple locking-free quasi-3D hyperbolic plate isogeometric method. (1st July 2017) - Liu, Shuo; Yu, Tiantang; Bui, Tinh Quoc; Yin, Shuohui; Thai, Duc-Kien; Tanaka, Satoyuki
Abstract: The paper presents an effective plate formulation based on isogeometric analysis (IGA) and a novel simple quasi-3D hyperbolic shear deformation theory (S-Q3HSDT) to study static bending, free vibration, and buckling behaviors of functionally graded plates. In S-Q3HSDT fashion, five unknowns per node are included; both shear deformation and thickness-stretching effects across the thickness are taken into account; and the awkward shear locking phenomenon is avoided. The requirement for C 1 -continuity in terms of the S-Q3DHSDT is straightforwardly possessed with the aid of inherent high-order continuity of non-uniform rational B-spline (NURBS), which serve as basis functions in our IGA formulation. The superior performance and accuracy of the proposed method is demonstrated through numerous numerical examples. The calculated results are then compared with reference solutions, investigating the effects of boundary conditions, gradient index, and other aspect ratios on mechanical responses of functionally graded plates.